High dynamic range single channel sampling of wideband RF signals using ultra‐fast nanoscale photoconductive switching. Issue 3 (1st February 2016) - Tripon‐Canseliet, C.; Zegaoui, M.; Jestin, G.; Coinon, C.; Berger, P.; Baili, G.; Descamps‐Mandine, A.; Maksimovic, I.; Decoster, D.; Hodé, J.M.; Dolfi, D.; Chazelas, J.
Abstract : This Letter reports on new experimental high dynamic range sub‐sampling performances obtained from nanoscale microwave photoconductive switches operating under a 0.8 µm wavelength pulsed illumination. Experimental results have been performed on different samples benefiting of a low temperature grown Gallium Arsenide absorbing layer on GaAs substrate, coplanar microwave electrode profile optimisation, and the use of an ultra‐low noise jitter optical source delivering optical pulses of 1 to10 ps pulse width at a 2 GHz repetition frequency at 0.8 µm optical wavelength. Thanks to carrier lifetime tunability achievement from 1 to 20 ps, in association with a carrier mobility of 3900 cm²/V.s, experimental demonstrations of 54 and 45 dB signal‐to‐noise ratio microwave signal sampling for signals at 5, 76 and 20 GHz frequency bandwidth respectively confirms submicron devices functionality as a new class of single channel photonic analogue to digital converters.